Sobrevida de pacientes após o transplante cardíaco e análise da qualidade de vida relacionada à saúde: dados de um centro transplantador brasileiro. - Wágner do Nascimento Carvalho (2019)
INTRODUCTION: Heart Failure (HF) is a serious public health problem and represents the main cause of hospitalizations for cardiovascular diseases within the Brazilian Sistema Único de Saúde. A potential treatment for patients with advanced form of the disease is Heart Transplantation (HT). However, complications after HT limit survival and impact on the Health Related Quality of Life (HRQoL) level. OBJECTIVE: To analyze the survival of patients undergoing HT, and the HRQoL level in the context of patients with HF and after HT. METHOD: Cohort study to analyze survival and cross-sectional analysis of HRQoL conducted in a Brazilian university hospital. Survival analysis was performed according to the Kaplan-Meier method, and the assessment of the HRQoL level through the World Health Organization Quality of Life - Bref questionnaire (WHOQOL-Bref), scoring each domain and level of perception of Quality of Life (QoL) and health on a Likert scale, which was later converted to a score between 0 and 100 points, the higher the score being the higher the HRQoL level. RESULTS: Survival analysis included 302 patients undergoing HT between the years 2006 and 2018, most of them male 205 (67.9%), median age 47 (38 - 57) years, non-white 205 (67.9 %), education level less than or equal to eight years of schooling 154 (61.1%), retired 157 (56.8%), per capita income 213 (81%) less than or equal to one minimum wage, most affected by Chagas heart disease 133 (44%), transplanted in emergency status 197 (65.2%). The per capita income variable impacted the analysis and showed that the higher the income the greater the likelihood of longer survival. Overall survival was 76.6% at one year after transplantation, 62.2% at five years and 58.2% at 10 years. A total of 186 patients participated in the HRQoL level assessment after HT, and had a median HRQoL level according to the WHOQOL-Bref questionnaire domains of 67.8 points for the physical domain, 83.3 for the psychological domain, 75 for the social relations domain, 71.9 for the environment domain, and 87.5 for the overall QoL and health level perception score. In the analysis comparing the HRQoL level between HT patients (n = 183) and patients with advanced HF (n = 79), patients undergoing HT showed a better level of HRQoL according to the WHOQOL-Bref questionnaire in all domains and perception of QoL level and health (p-value <0.001). CONCLUSION: In this study, the survival of patients undergoing HT had an influence on per capita income, and the higher the income higher the probability of survival. After HT they had a HRQoL score in all domains of the QoL questionnaire with a median greater than or equal to 67.8 points. Patients after HT compared with HF patients had a better level of HRQoL in all analyzes performed.